1999
DOI: 10.1038/35005523
|View full text |Cite
|
Sign up to set email alerts
|

ICOS is an inducible T-cell co-stimulator structurally and functionally related to CD28

Abstract: otherwise fatal overstimulation of the lymphoid system 6-9 . Here we report the identification of a third member of this family of molecules, inducible co-stimulator (ICOS), which is a homodimeric protein of relative molecular mass 55,000-60,000 (M r 55K-60K). Matching CD28 in potency, ICOS enhances all basic Tcell responses to a foreign antigen, namely proliferation, secretion of lymphokines, upregulation of molecules that mediate cell-cell interaction, and effective help for antibody secretion by B cells. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
862
6
20

Year Published

1999
1999
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(915 citation statements)
references
References 29 publications
27
862
6
20
Order By: Relevance
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The IL-10-secreting phenotype was stably maintained during T cell cloning, but secretion was, to a large extent, dependent on ICOS signaling, which is in agreement with previous reports [28][29][30][31]. Of note, studies in ICOS-deficient mice have revealed a key role for this costimulatory molecule in Tdependent B cell responses [24,25].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have identified ICOS as an important regulator of IL-10 production [28][29][30][31], and as shown in Fig. 2, expression of this costimulatory molecule was maintained on T FH cells during co-culture with B cells.…”
Section: Icos-mediated Regulation Of Il-10 Production By T Fh Cell-dementioning
confidence: 57%
“…41 CD28 enhances T-cell functions essential for effective antigen-specific immune responses, whereas CTLA-4 counterbalances the CD28-mediated signals and thus prevents overstimulation of the lymphoid system. 41 A newer member of this family of costimulatory receptors, 'inducible costimulator' (ICOS), was identified by Hutloff et al 42 Unlike the constitutively expressed CD28, ICOS is induced on the T-cell surface and functions to predominantly upregulate interleukin (IL)-4 as opposed to IL-2. 43 Recent sequence analysis demonstrated that the CD28, CTLA-4, and ICOS genes locate telomerically in this order in B230-kb region on chromosome 2q33.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stimulation by TNF/TNFR family members, interaction of ICOS [4], which is a member of the B7 family of costimulatory molecules, with its ligand [5] has also an important role in B cell physiology. ICOS is expressed on both CD4 + and CD8 + activated T lymphocytes [6]. ICOS is essential for T cell-dependent B cell responses [7][8][9] and the GC reactions [10,11].…”
Section: Light Stimulation Enhances Ig Secretionmentioning
confidence: 99%